Memory bias in anorexia nervosa: Evidence from directed forgetting - TOPÇUOĞLU, VOLKAN (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
The aim of this study was to examine memory bias for disorder-relevant information in anorexia nervosa by using the directed forgetting paradigm. Normal controls and patients with anorexia nervosa were given a list consisting of neutral and disorder-relevant words, which they were either asked to remember (R) or forget (F). Memory performance was measured by a free recall and a Yes/No recognition task for all items. There was a directed forgetting effect for both groups; however, the magnitude of the effect (difference between R and F words) was smaller for the patient group due to higher recall of F items. Further analyses showed that this was true only for disorder-relevant but not for neutral items. Our findings support the existence of a strong memory bias for disorder-relevant information in patients with anorexia nervosa, who had difficulty in avoiding the processing of information that they were asked to forget. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: memory bias; anorexia nervosa; eating disorders; directed forgetting; information processing; OBSESSIVE-COMPULSIVE DISORDER; EATING-DISORDERS; QUANTITATIVE MEASURE; EXPLICIT MEMORY; STROOP TEST; INFORMATION; WORDS; SHAPE; PSYCHOPATHOLOGY; FORBIDDEN